Associations between a composite score of hemoglobin, CRP and albumin and physical performance in older patients undergoing gastrointestinal cancer surgery. (December 2021) - Egenvall, Monika; Karlsson, Emelie; Nygren-Bonnier, Malin; Franzén, Erika; Rydwik, Elisabeth
Summary: Background & aims: Abnormal levels of hemoglobin, C-reactive protein (CRP) and albumin are common in people with gastrointestinal cancer. The hypothesis was that this is of importance for physical performance in older persons in the perioperative context. Thus, the aim was to evaluate the association between hemoglobin, CRP and albumin and physical performance before and after abdominal cancer surgery in older patients. Methods: Patients ≥70 years of age scheduled for abdominal cancer surgery were invited to take part in the study. Data on levels of hemoglobin, CRP and albumin and physical performance (Six-Minute Walk Test, functional leg strength [chair-stands completed in 30 s], and maximal inspiratory muscle strength), were collected at baseline (n = 178) and physical performance was reassessed before discharge (n = 120). A composite score of 0–3 points was used, based on the presence or not of anemia, elevated CRP or hypoalbuminemia. Multivariable linear regressions were used for statistical analysis. Results: Before surgery, walking distance in patients scoring 2–3 (presence of 2 or 3 abnormal values) was shorter in comparison to patients scoring 0 (all values within normal range) in the multivariable model (−39.1 m; 95% CI -74.2,  −3.9, p = 0.030). The number of chair stands performed during 30 s was lower in patients scoring 1 (−1.7; 95% CI -3.2,  −0.2, p = 0.028) and 2–3 (−1.6; 95% CI -3.0,  −0.1, p = 0.037) compared to patients scoring 0. No significant differences were seen between score groups and inspiratory muscle strength. After surgery, no differences were seen in walking distance or chair stands between patients with different scores. Conclusions: Older patients with abnormal concentrations of hemoglobin, CRP and albumin before gastrointestinal cancer surgery showed impaired physical performance before surgery. Knowledge about potentially modifiable factors prior to cancer surgery increases the possibility to prepare the individual, which in turn might contribute to reduced morbidity and faster recovery after surgery.